Perancangan UI/UX Fitur Asrama Mahasiswa Berbasis Website dengan Pendekatan User Centered Design - Fika Febrika; Pacu Putra Suarli; Nabila Rizky Oktadini; Allsela Meiriza; Putri Eka Sevtiyuni; Endang Lestari Ruskan; Dedy Kurniawan (STMIK Budi Darma, 2023)
The rapid development of information technology makes easier for human accessing and exchanging information through digital media like websites. Since 2019, Badan Pengelola Usaha Universitas Sriwijaya started developing student dormitories booking system, namely Fitur Asrama Mahasiswa. This system can be accessed by Sriwijaya University students via bpu.unsri.ac.id. The types of dormitories shown in this feature consist of apartments, flats, and government dormitories. Based on interviews, it was stated that users still had difficulty accessing Fitur Asrama Mahasiswa, especially in user interface and user experience, so it was necessary to improve interface design with aim of making it easier for users to find information and book dorm room. Design improvement of Fitur Asrama Mahasiswa bpu.unsri.ac.id interface carried out through design process usingUser Centered Design (UCD) approach, so thataccommodate user needs. Design process begins with commitment from bpu unsri to involve users in design process through discussion. Then, determine the context of use through interviews, determine user needs and organizational needs through usability testing and interviews, interface designs based on user needs, and evaluate designsthrough usability testing. Using the UCD approach proven that system usability increased which consists of four parameters, namely success rate, efficiency, error rate, and satisfaction. Success rate increased from 52.86% to 94.76%. Efficiency increased from 45.12% to 96.05%. The error rate decreased from 50.12% to 3.69&. Satisfaction increased from 32.5 to 87.33